Epigallocatechin-3-Gallate Protects H2O2-Induced Nucleus Pulposus Cell Apoptosis and Inflammation by Inhibiting cGAS/Sting/NLRP3 Activation - Tian Y; Bao Z; Ji Y; Mei X; Yang H (Dove Medical Press, 2020)
Yixing Tian, Zhaohua Bao, Yiming Ji, Xin Mei, Huilin Yang Department of Orthopedic Surgery, The First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, People’s Republic of ChinaCorrespondence: Huilin Yang Email suzhouspine@163.comBackground: Intervertebral disc degeneration (IDD) is the most common diagnosis of patients with lower back pain. IDD is the underlying lesion of many spinal degenerative diseases; however, the role of cGAS/Sting/NLRP3 pathway and epigallocatechin gallate (EGCG) in the development of IDD remained unclear.Methods: The expressions of cGAS, Sting and NLRP3 mRNA of intervertebral disc (IVD) samples from IDD patients and controls were detected by RT-PCR. The nucleus pulposus cells (NPCs) were induced by hydrogen peroxide (H2O2) and used as an in-vitro model. Both 5 μM and 25 μM EGCG treatment were used to detect the effect of EGCG on the in-vitro model. Cell viability was detected by the MTT method, and cell apoptosis and cell cycle would be detected by flow cytometry. Western blot was used in the detection of the expression of cGAS/Sting/NLRP3 as well as apoptosis-related protein level. ELISA was used in the detection of pro-inflammatory factors, including IL-1β, TNF-α, IL-6 and IL-10.Results: The expressions of cGAS, Sting and NLRP3 mRNA were significantly increased in the IVD samples from IDD patients and NLRP3 was associated with cGAS and Sting. Advanced in-vitro study showed that H2O2 significantly increased the expression of cGAS, Sting and NLRP3 protein levels. Advanced experiments showed that EGCG treatment demonstrated significant protective effects in cell viability, apoptosis, cell cycle arrest and inflammatory status through down-regulation of cGAS/Sting/NLRP3 pathway.Conclusion: It was shown that the cGAS, Sting and NLRP3 up-regulation was associated with the incidence of IDD. Our findings also suggest that EGCG treatment would provide anti-apoptosis, anti-inflammation and promote cell viability in H2O2 treatment-incubated NPCs through inhibiting cGAS/Sting/NLRP3 pathway.Keywords: intervertebral disc degeneration, nucleus pulposus cells, epigallocatechin gallate, cGAS, sting, NLRP3